New Frontiers of Entrepreneurship - Iqbal M. Khan (Karachi Oxford University Press, 2017)
The book introduces the subject of entrepreneurship and presents a holistic view of its various dimensions, particularly in the context of South Asia, and more specifically Pakistan.
Foreword by J. Hanns Pichler
Keywords: New business enterprises--Management -- Pakistan -- Entrepreneurship